The Brittle Rachis Trait in Species Belonging to the Triticeae and Its Controlling Genes Btr1 and Btr2 - Zeng, Xiaoxue; Mishina, Kohei; Jia, Juqing; Distelfeld, Assaf; Maughan, Peter Jeff; Kikuchi, Shinji; Sassa, Hidenori; Komatsuda, Takao (Frontiers in Plant Science, 2020)
In many non-cultivated angiosperm species, seed dispersal is facilitated by the shattering of the seed head at maturity; in the Triticeae tribe, to which several of the world’s most important cereals belong, shattering takes the form of a disarticulation of the rachis. The products of the genes Btr1 and Btr2 are both required for disarticulation to occur above the rachis nodes within the genera Hordeum (barley) and Triticum/Aegilops (wheat). Here, it has been shown that both Btr1 and Btr2 are specific to the Triticeae tribe, although likely paralogs (Btr1-like and Btr2-like) are carried by the family Poaceae including Triticeae. Aegilops tauschii (the donor of the bread wheat D genome) lacks a copy of Btr1 and disarticulation in this species occurs below, rather than above the rachis node; thus the product of Btr1 appears to be required for disarticulation to occur above the rachis node.